Sosialisasi Bahaya Narkotika sebagai Bentuk Kenakalan Remaja di kalangan Siswa SMKN 1 Kecamatan Kragilan Kabupaten Serang - Hibar, Ujang; Husni, Mohamad; Trihandriyanto, Nova; Rini, Ratu Yustika; Rohaeni, Nani; Arifin, Suherman; Dahlia, Fissilmi; Hidayat, Chaerul; Putri, Rindi Dwi; Luthviah, Shiva Durrotu; Nurkhasanah, Siva Aprilia; Mardiana, Rani (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Narcotics are a substance that is very dangerous if its use is misused and permission is not obtained from the authorities, narcotics will damage the nation's next generation who will run the government in the future. The rise in the use of narcotics is in line with the influx of globalization and modernization which makes it easier for people to obtain them as well as a network of dealers who are aggressively looking for marketing targets among young people who are susceptible to sweet advances and do not yet have clear life principles. Indonesia is one of the countries that is fighting drug dealers, users and networks, this is because every 17 seconds someone is arrested for violating drug-related laws. Indonesia has 2 laws that regulate the misuse of narcotics, namely Law No. 35 of 2009 and Law No. 5 of 1997. All of them are clear about the sanctions and dangers of using narcotics, the punishment can even be death. This service journal refers to biological theory which explains the biological theory of the brain, metabolic imbalance theory, and genetic theory. Many experts, especially biological experts, say that narcotics will damage brain growth and development. This service journal uses literature and seminar methods which are expected to provide an explanation of a situation where an individual or person will have a bleak future if they fall into the use of narcotics because it will damage brain tissue and damage the body. As early as possible, we will unite together to fight against narcotics, not only for law officers who work, but all elements of society are involved in fighting the use of narcotics which has penetrated young people, especially among teenagers who are still at school, who are vulnerable to the temptation of using narcotics.